Kebutuhan Riil Tenaga Perawat dengan Metode Workload Indicator Staff Need (WISN) - Ni Luh Ade Kusuma Ernawati; Nursalam Nursalam; Lilik Djuari (Universitas Airlangga, 2011)
Introduction: Nurses are health workers in hospitals that provide nursing care to patients for 24 hours. Workload of nurses was high due to insufficient numbers of nurses. It will have an impact on the decrease in work productivity that may affect nurses care for patients. To get the human resources necessary to suit the needs of nursing manpower planning to increase the competitiveness of hospitals in the era of globalization. The research objective was to analyze the real needs of nurses on staff workload indicators need (WISN).Method: The study design was observational analytic. Analysis of workload using the method of approach to time and motion study. Sample were 24 nurses who met the inclusion criteria. Analysis of the needs of staff nurses using the workload indicators need (WISN).Result: The results obtained based on the calculation of nurses with WISN method needs of nurses in the medical-surgical nurses as many as 54 people. Objective workload of nurses in the room medical surgery general state hospital of Bali is the average 82.61%, including height. The total time required to complete the productive activities of more than 80%.Conclusion: Conclusion of this study show the number of nurses in the medical-surgical general hospital bali is still lacking as many as 30 people. It is suggest to the hospital management to increase gradually the number of nurses in the medical room.